The antibiofilm activity of purified and characterized mannan from Saccharomyces cerevisiae against multidrug-resistant Escherichia coli - Naam Fadhil Abbas Al-Helli; Jehan Abdul Sattar Salman (Novel Research in Microbiology Journal, 2023)
Biofilm formation by Escherichia coli presents a major challenge in the clinical settings, resulting in persistent infections and treatment failures. These bacterial communities, protected by a matrix, resist antibiotics and immune responses, thus causing a prolonged challenge to treat such infections. Developing effective strategies against E. coli biofilms is crucial for improving the patient outcomes and reducing the burden on the healthcare systems. This study aimed to extract, purify, and characterize mannan from Saccharomyces cerevisiae, then its antibiofilm activity was evaluated against the multi-drug resistant E. coli (MDR-E. coli) isolates obtained from various clinical sources (i.e., urine, stool, wound, and catheter). Using a standardized protocol with slight modifications, the crude mannan extraction yielded 37.6 %, and subsequent purification achieved an efficiency of 99.6 %. Characterization assays of the purified mannan included FT-IR; FE-SEM, carbohydrate content estimation, solubility, and melting point tests, which revealed the presence of α-1,6 and α-1,2 linked sugars; crystalline nature, high porosity (80 %) carbohydrate content, high solubility in water, and a melting point of 248 °C. The purified mannan exhibited a substantial ability to inhibit biofilm formation (37.50 %) and degrade the existing MDR-E. coli biofilms (37.43 %). These findings underscore the potential of S. cerevisiae mannan as an effective antibiofilm agent for the clinical applications. Further exploration and optimization of the mannan's therapeutic potential are essential to fully leverage its efficacy in combating the biofilm-associated infections caused by MDR-E. coli.